Understanding the idea of law in a sample of children and adolescents in the city of Bucaramanga (Colombia) (Revista de Investigaciones Universidad del Quindío, 2013)
The aim of this cross-sectional descriptive study was to investigate the characteristics and changes in the understanding of the idea of law in a sample of 250 children and adolescents-half of each gender-, aged between 9 and 17. We used the Piagetian clinical interview. The results confirm findings by previous studies: The idea of the law between 9 and 10 years old is personalistic, immutable, generic, moral, punitive, unfair and perennial, is associated with the promises and lies. Between 11 and 13 years old, to the law it can handle and cannot exert its effect or do asynchronous and incontingently, is seen as a mechanism of organizing society through punishment. Between 14 and 17 years, the law organizes public and private life of individuals, is more than a moral standard, legal and social effects, administers sanctions, guarantees rights but so incontingent, asynchronous, disproportionate. The law is modified, manipulated, trespassable and not always used to be enforced. In the ten years later is the action of the law in terms of the possibilities and probabilities of each case.
Keywords: Development; law; adolescent; children; mental representation